2015
DOI: 10.1186/s40645-015-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of fine-grained sediments in the Yangtze River and the implications for provenance and chemical weathering in East Asia

Abstract: In order to interpret the marine clastic record preserved in the sedimentary basins of the East Asian marginal seas, it is important to understand how sediment transport and chemical weathering affect the composition of sediment enroute to its sink. Here we present a new data set for fine-grained sediment (<63 μm) from the Yangtze River and its major tributaries, which represents a baseline for interpreting sediment in the East China Sea. We demonstrate that there is no significant coherent downstream variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…Thus, the effects of eroded sediments on the ESR signal intensity values observed in the middle to lower parts could explain the departures between predicted and analyzed ESR values in these sections of the mainstream. He et al (2015), in a study of the geochemistry of riverbed sediments in the Yangtze basin, reported that Nd and Sr isotope ratios varied in different parts of the Yangtze depending on the nature of the geological block(s) in each part of the basin and that the riverbed sediments in the middle to lower parts of the mainstream were derived mainly from the Songpan-Garze terrane and Yangtze Block; this result is consistent with our results shown in Fig. 8a.…”
Section: Classification Of Tributaries Based On Esr Signal Intensity supporting
confidence: 82%
“…Thus, the effects of eroded sediments on the ESR signal intensity values observed in the middle to lower parts could explain the departures between predicted and analyzed ESR values in these sections of the mainstream. He et al (2015), in a study of the geochemistry of riverbed sediments in the Yangtze basin, reported that Nd and Sr isotope ratios varied in different parts of the Yangtze depending on the nature of the geological block(s) in each part of the basin and that the riverbed sediments in the middle to lower parts of the mainstream were derived mainly from the Songpan-Garze terrane and Yangtze Block; this result is consistent with our results shown in Fig. 8a.…”
Section: Classification Of Tributaries Based On Esr Signal Intensity supporting
confidence: 82%
“…(a) Schematic map showing the Changjiang drainage basin and (b) a cartoon showing the relative position of tributaries, lakes, and gauging stations. Red stars display sampling sites of this study, and circles represent sampling sites for data collected from literatures (Ding et al, ; He et al, ; Yang et al, , ). TGD = Three Gorges Dam.…”
Section: Introductionmentioning
confidence: 99%
“…Scudder et al (2016) summarize the geochemical and statistical techniques that can be used to determine the composition of dispersed ashes and quantify their contribution to such ocean sediments. Combined with the results provided by He et al (2015), their method is particularly useful for evaluating the origins and relative contributions of finegrained siliciclastic sediments to the hemipelagic sediments of the East China and Japan seas.…”
mentioning
confidence: 99%
“…Twelve oral and four poster presentations were given at the special JpGU session, and the papers presented in this issue include three research articles and six reviews based on presentations from that session. These nine papers cover the evolution and variability of the Asian monsoon , the evolution of surface water and deep-water circulation in East Asian marginal seas (Gallagher et al 2015;Kim et al 2015;Itaki 2016), the impact of the East Asian summer monsoon on the composition of sediment discharged from the Yangtze River, surface water salinity in the East China Sea, flood records and typhoon tracks in southern Japan (He et al 2015;Horikawa et al 2015;Suzuki et al 2016), and volcanic ash as a useful tool for land-ocean correlation and as a significant source of sedimentary material in the northwest Pacific Ocean (Ikehara 2015;Scudder et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation